The role of contracting schemes for the welfare costs of nominal rigidities over the business cycle - Matthias Paustian (Deutsche Bundesbank, 2005)
What is the role of contracting schemes for the welfare costs of nominal rigidities over the business cycle? We examine 4 different modeling schemes of nominal rigidities that all have the same average duration of contracts. We find that Calvo (1983) wage and price contracts may deliver welfare costs that are 3-4 times higher than Taylor (1980) contracts. However, that result is sensitive to the monetary policy rule. We discuss the implications of modeling capital mobility and of adopting the Mankiw and Reis (2002) sticky information scheme for the welfare costs of nominal rigidities.
Keywords: E32; E52; 330; welfare; Calvo; Taylor; sticky information; costs of nominal rigidities; Geldpolitik; Lohnrigidität; Lohnbildung; Wohlfahrtseffekt; Theorie